2006
DOI: 10.1021/ja063201x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Bifunctionality of Chiral Thiourea-Based Organocatalysts:  Competing Routes to C−C Bond Formation

Abstract: The mechanism of enantioselective Michael addition of acetylacetone to a nitroolefin catalyzed by a thiourea-based chiral bifunctional organocatalyst is investigated using density functional theory calculations. A systematic conformational analysis is presented for the catalyst, and it is shown that both substrates coordinate preferentially via bidentate hydrogen bonds. The deprotonation of the enol form of acetylacetone by the amine of the catalyst is found to occur easily, leading to an ion pair characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
215
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(239 citation statements)
references
References 27 publications
18
215
0
6
Order By: Relevance
“…Theoretical study of the Hg 2+ recognition by 1,3-diphenylthiourea has been reported [2]. The mechanism of enantioselective Michael addition of acetylacetone to a nitroolefin catalyzed by a thiourea based chiral bifunctional organocatalyst is investigated using density functional theory calculations [3]. Yang et al [4] reported the structural and spectroscopic study of N-2-fluorobenzoyl-N'-4-methoxyphenyl thiourea.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical study of the Hg 2+ recognition by 1,3-diphenylthiourea has been reported [2]. The mechanism of enantioselective Michael addition of acetylacetone to a nitroolefin catalyzed by a thiourea based chiral bifunctional organocatalyst is investigated using density functional theory calculations [3]. Yang et al [4] reported the structural and spectroscopic study of N-2-fluorobenzoyl-N'-4-methoxyphenyl thiourea.…”
Section: Introductionmentioning
confidence: 99%
“…[22] In the first, called Pathway A, the nucleophilic nitromethide anion is coordinated to the positivelycharged trialkylammonium, while the aldehyde electrophile is coordinated to the thiourea moiety ( Figure 4). In the second binding mode, called Pathway B, the opposite coordination pattern is found ( Figure 5).…”
mentioning
confidence: 99%
“…12b The protonated tertiary amine then directs the nucleophile to attack from the less hindered face. In a theoretical study, Pápai and Sóos showed 13 that while calculations do support this, and also explain the preferred stereochemistry of the product, an opposite coordination scheme is not only possible, but in fact energetically slightly more favorable. …”
Section: Issn 1551-7012mentioning
confidence: 97%